Anionic nanoparticle-lipid membrane interactions: the protonation of anionic ligands at the membrane surface reduces membrane disruption. Issue 25 (7th May 2019) - Salassi, Sebastian; Canepa, Ester; Ferrando, Riccardo; Rossi, Giulia
Abstract : The interaction between anionic Au nanoparticles and model lipid membranes is facilitated by the spontaneous protonation of the NP ligand carboxylate groups, COO − ˙ → COOH, in the lipid headgroup region. Abstract : Monolayer-protected gold nanoparticles (Au NPs) are promising biomedical tools with applications in diagnosis and therapy, thanks to their biocompatibility and versatility. Here we show how the NP surface functionalization can drive the mechanism of interaction with lipid membranes. In particular, we show that the spontaneous protonation of anionic carboxylic groups on the NP surface can make the NP-membrane interaction faster and less disruptive.